Evaluation of an HIV-related Education Intervention Scale-up: A Hybrid Type 3 Effectiveness-implementation Study in the Dominican Republic. - Stonbraker, Samantha Brown; Castro, Yazmina Espiritusanto; Caraballo, Pamela Baez; Mayorga, Stefanie; Rael, Christine Tagliaferri; Dunn, Maria; Centi, Sophia; McNair, Bryan; Michel, Jacob; Goggin-Kehm, Molly; Arcia, Adriana; Cook, Paul (AIDS & Behavior, 2025)
We developed an infographic intervention to augment HIV-related education in the Dominican Republic (DR), which demonstrated preliminary success in pilot studies. We then partnered with the United States Agency for International Development's (USAID) HIV Services and Systems Strengthening program in the DR to scale up the intervention. We used a two-tier Training-of-Trainer (TOT) method to teach intervention administration. N = 12 program leaders completed the tier-1 training and subsequently taught N ~ 102 clinical staff to use infographics with people with HIV (PWH) (tier-2 trainings). Study Aim 1 was to assess implementation outcomes; Aim 2 was to explore infographic influences on program-level health outcomes. We conducted a hybrid type 3 effectiveness-implementation study with three data components: (1) Surveys bookending tier-1 and tier-2 trainings; (2) Focus groups with tier-1 and tier-2 trainees; and (3) program-level data. We designed surveys according to Kirkpatrick's Training Evaluation Model and analyzed responses with descriptive statistics and/or Fisher's exact tests. We led four focus groups with a theory-driven guide and analyzed transcripts with conventional qualitative content analysis. We analyzed program-level data by comparing outcomes before and after infographic use with advanced statistical modeling. All 12 program leaders completed tier-1, and 36 staff completed tier-2 surveys; focus groups comprised eight tier-1 and 27 tier-2 trainees; program-level data pertained to 4,318 PWH. Surveys and focus groups indicated the TOT method is feasible, acceptable, and sustainable. Program-level findings showed PWH were more likely to attend scheduled visits and be virally suppressed following infographic implementation. Results indicate our intervention can likely enhance HIV education at large scale.